Estudo dos ataques matemáticos ao RSA e hipótese de modificação do algoritmo - García López, Javier (2004)
This article presents a brief study on the public key algorithm RSA and its vulnerabilities, setting some changes in it, taking advantage on certain well known numeric properties. This new version of the algorithm is going to be tested, compared to the original RSA, on the key generation, cipher, decipher, attacks and the final results are presented and evaluated, focusing the impact generated by the algorithm change.